2015
DOI: 10.1021/acs.joc.5b01536
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Copper(I)-Catalyzed 5-Iodo-1,2,3-triazole Formation from Azide and Terminal Alkyne

Abstract: 5-Iodo-1,2,3-triazole (iodotriazole) can be prepared from a copper(I)-catalyzed reaction between azide and terminal alkyne in the presence of an iodinating agent, with 5-protio-1,2,3-triazole (protiotriazole) as the side product. The increasing utilities of iodotriazoles in synthetic and supramolecular chemistry drive the efforts in improving their selective syntheses based on a sound mechanistic understanding. A routinely proposed mechanism takes the cue from the copper(I)-catalyzed azide-alkyne cycloaddition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 44 publications
1
25
0
4
Order By: Relevance
“… 39 Under solvent-based conditions, Cu–NHC complexes can be synthesized by the reaction of metallic Cu(0) with imidazolium salts, although these reactions require a large excess of insoluble Cu(0) and long reaction times. 40 Recently, Lamaty and co-workers reported that Cu–NHC complexes ( 2 ) could be synthesized from imidazolium salts ( 1 ) and metallic copper using a planetary ball mill ( Scheme 2 ). 41 The rate of reactions was enhanced due to the high concentration of reagents and the highly efficient mixing under mechanochemical conditions.…”
Section: Reduced Reaction Timesmentioning
confidence: 99%
“… 39 Under solvent-based conditions, Cu–NHC complexes can be synthesized by the reaction of metallic Cu(0) with imidazolium salts, although these reactions require a large excess of insoluble Cu(0) and long reaction times. 40 Recently, Lamaty and co-workers reported that Cu–NHC complexes ( 2 ) could be synthesized from imidazolium salts ( 1 ) and metallic copper using a planetary ball mill ( Scheme 2 ). 41 The rate of reactions was enhanced due to the high concentration of reagents and the highly efficient mixing under mechanochemical conditions.…”
Section: Reduced Reaction Timesmentioning
confidence: 99%
“…For the synthesis of the target radical PTM-Fc dyad (3-Rad) a copper-catalyzed azide-alkyne cycloaddition (CuAAC) click chemistry strategy was envisaged. [53][54][55] The standard conditions for the click reaction that generates in situ the copper(I) catalyst by reduction of CuSO 4 using ascorbic acid or ascorbate 56 could not be used here because the ascorbic acid reduces the radical to the anion that in turn is irreversibly protonated to the aH form. 57 Therefore, as mentioned above, before performing the reaction on the surface, the synthetic procedure was optimized in solution.…”
Section: Functionalization Of Ptm Radical Molecules Via Click Chemistmentioning
confidence: 99%
“…Therefore, the mechanistic understanding of internal alkyne CuAAC reactions is influenced by evolving insights into terminal alkyne CuAAC reactions. The mechanisms of reactions involving iodoalkyne and gold(I) acetylide have been studied in more detail than others 60. At this point, it is reasonable to say that most of these reactions, if not all, adopt similar catalytic cycles to that shown in Scheme , with the internal alkyne substrate R–C≡C–X replacing the copper acetylide (R–C≡C–Cu); hence with X replacing one of the copper centers in the dinuclear model.…”
Section: Cuaac Reactions Involving Internal Alkynesmentioning
confidence: 99%